Long term survival analysis of cementless Spotorno femoral stem in young patients - Murat Mert; Cenk Ermutlu; Emrah Kovalak; Ethem Ünkar; Sibel Çağlar Okur (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to analyze the survivorship and clinical outcome of Cementless Spotorno (CLS) stem in young patients. Methods: A total of 99 consecutive hip arthroplasties using CLS stem were performed on 84 patients younger than 50 years of age between 1993 and 2001. 63 patients were available for final follow-up (mean age: 39 ± 7.8 (range: 22–50)). Patients' Harris Hip Scores (HHS) and survivorship estimates were calculated. Radiographs were analyzed for acetabular implant status, canal fill index (CFI), stem alignment, osteolysis, and stress shielding. Results: Mean follow-up time was 18 years (13–3), and mean HHS was 88.7 (58–100). Patients with femoral neck fracture had a more favorable functional outcome (p = 0.027), while those with stems in varus had lower scores (p = 0.017). 31 stems (49%) were undersized and 30 hips (47%) had perifemoral osteolysis. Acetabular impairment was strongly associated with osteolysis in Gruen zones 1 and 7 (p < 0.01). Seventeen of the osteolytic lesions occurred in Gruen zone 1, 4 lesions in zone 2, 9 in zone 6 and 22 in zone 7. Forty nine stems were well aligned, 10 were in varus and 5 in valgus. Six patients presented with grade 1 stress shielding, 42 with grade 2, 9 with grade 3 and 7 with grade 4. Pedestal formation was evident in 13 cases. Kaplan-Meier survivorship estimates at 18 years with revision for any reason as the end point and with septic revisions excluded were 91.2% (95% CI: 83.7%–98.7%) and 95.1% (95% CI: 89.5%–100%), respectively. There was no difference between survival estimates of patients with different etiologies. Conclusion: CLS stems in young patients have high survival estimates in the long term with good-excellent results. Spotorno stems perform equally well in all etiologies with no difference in terms of survivorship. Level of Evidence: Level IV Therapeutic study. Keywords: Hip arthroplasty, Spotorno, Survivorship, Gruen, Osteolysis